Stunting Incidence In Toddlers At West Dompu Health Center Dompu Regency - Mirham Nurul Hairunis (Sean Institute, 2023)
Stunting or stunted children (short) is a condition in which children experience chronic nutritional problems, with the results of measuring length or height that is less than minus two standard deviations of median child growth standards from WHO. Toddlers with stunting are at risk of experiencing impaired growth and development in their lives. The aim of this study was to determine the picture of stunting incidence in toddlers at the West Dompu Health Center, Dompu Regency. This type of research is descriptive qualitative, namely to describe the incidence of stunting in toddlers at the West Dompu Health Center, Dompu Regency. The research location is at the West Dompu Health Center, Dompu Regency. The measuring instrument used is the Z-score table of WHO nutritional status. The sampling technique used was a total sampling of 512 toddlers.